Circulating extracellular particles from severe COVID-19 patients show altered profiling and innate lymphoid cell-modulating ability - Forte, Dorian; Pellegrino, Roberto Maria; Trabanelli, Sara; Tonetti, Tommaso; Ricci, Francesca; Cenerenti, Mara; Comai, Giorgia; Tazzari, Pierluigi; Lazzarotto, Tiziana; Buratta, Sandra; Urbanelli, Lorena; Narimanfar, Ghazal; et al. (Frontiers in Immunology, 2023)
Extracellular vesicles (EVs) and particles (EPs) represent reliable biomarkers for disease detection. Their role in the inflammatory microenvironment of severe COVID-19 patients is not well determined. Here, we characterized the immunophenotype, the lipidomic cargo and the functional activity of circulating EPs from severe COVID-19 patients (Co-19-EPs) and healthy controls (HC EPs) correlating the data with the clinical parameters including the partial pressure of oxygen to fraction of inspired oxygen ratio (PaO2/FiO2) and the sequential organ failure assessment (SOFA) score. We observed that EPs from severe COVID-19 patients: 1) display an altered surface signature as assessed by multiplex protein analysis; 2) are characterized by distinct lipidomic profiling; 3) show correlations between lipidomic profiling and disease aggressiveness scores; 4) fail to dampen type 2 innate lymphoid cell (ILC2s) cytokine secretion. As a consequence, ILC2s from severe COVID-19 patients show a more activated phenotype. In summary, these data highlight that abnormal circulating EPs promote ILC2-driven inflammatory signals in severe COVID-19 patients and support further exploration to unravel the role of EPs (and EVs) in COVID-19 pathogenesis.